Nitrogen and phosphorus exchanges between water, sediment and macrophytes in Lake Onalaska of Pool No. 7, Upper Mississippi River, 1975 to 1976 - Strodthoff, Kristine Marie (My University, 1978)
A study was conducted during 1975 and 1976 to determine the annual cycling of nitrogen and phosphorus at three sites in Lake Onalaska of the Mississippi River - Pool No. 7. Water, sediments and aquatic macrophyte species were collected and analyzed for nitrogen and phosphorus to establish the pattern of cycling.